Dryinidae of the Neotropical region (Hymenoptera: Chrysidoidea) - Olmi, Massimo (2014)
An updated revision of Neotropical Dryinidae is presented. Seven subfamilies, 23 genera and 502 species are treated. Descriptions, geographic distribution, known hosts, natural enemies and type material of each species are presented, together with illustrations of the main morphological characters and keys to the subfamilies, genera and species. Complete lists of references concerning the Neotropical Dryinidae and their hosts are given. The following new genus is described: Peckius Olmi & Virla, gen. nov. (Apodryininae). The following new species are described: Anteon xochipalense Olmi & Virla, sp. nov. (Mexico, Guerrero), Deinodryinus levigatus Olmi & Virla, sp. nov. (Peru, Lamabayeque), Deinodryinus xanthonotatus Olmi & Virla, sp. nov. (French Guiana), Dryinus semiruber Olmi & Virla, sp. nov. (Argentina, Corrientes), Dryinus valens Olmi & Virla, sp. nov. (Dominican Republic, Pedernales), Dryinus xanthopus Olmi & Virla, sp. nov. (French Guiana), Megadryinus cacaonis Olmi & Virla, sp. nov. (Brazil, São Paulo), Gonatopus isabelensis Olmi & Virla, sp. nov. (Ecuador, Galapagos Islands), Gonatopus villamilensis Olmi & Virla, sp. nov. (Ecuador, Galapagos Islands), Neodryinus mayanus Olmi & Virla, sp. nov. (Honduras), and Peckius insularis Olmi & Virla, sp. nov. (Ecuador, Galapagos Islands). The following new synonymies are presented: Deinodryinus kawensis Olmi 2011b (April) (=D. caxiuana Coelho, Aguiar & Engel, 2011 (June), syn. nov.); Dryinus gibbosus Olmi, 1984 (=D. multicarinatus Coelho, Aguiar & Engel, 2011, syn. nov.); Dryinus striatus (Fenton, 1927), (=D. sinopensis Olmi, 1984, syn. nov.; = D. cerrensis Olmi, 2004a, syn. nov.); Gonatopus Ljungh, 1810 (=Trichogonatopus Kieffer, 1909, syn. nov.); Eucamptonyx dromedarius (Cameron 1888) (=E. hansoni Olmi, 1991, syn. nov.); Haplogonatopus hernandezae Olmi, 1984 (=H. crucianus Olmi, 1986, syn. nov.). The following new combinations are established: Eucamptonyx dromedarius (Cameron, 1888), comb. nov. (from Gonatopus); Gonatopus goiasensis (Olmi 1991), comb. nov. (from Trichogonatopus); G. hispidus (Olmi 1984), comb. nov. (from Trichogonatopus); G. longinoi (Olmi, 1998d), comb. nov. (from Trichogonatopus); G. marinoae (Virla, 1997), comb. nov. (from Trichogonatopus); G. neotropicus (Olmi, 1984), comb. nov. (from Trichogonatopus); G. raptor (Fenton, 1927), comb. nov. (from Chalcogonatopus); G. rubriceps (Kieffer, 1909), comb. nov. (from Trichogonatopus); G. stellaris (Virla, 1997), comb. nov. (from Trichogonatopus). The male of Crovettia brasiliana Olmi 1984, is described for the first time.